2018
DOI: 10.1007/978-3-319-72332-7_49
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Phase Formation in Mg–Al–C Alloys Applied to Grain Refinement

Abstract: Grain refinement of Mg-Al based alloys is challenging because it is known that Zr, which is extremely effective in many Al-free alloys, cannot be used. The addition of carbon through various routes by using carbon-containing sources is considered as an option. The grain refinement mechanisms are still under debate. The present work is focused on the ternary base system Mg-Al-C, including the potential nucleants Al4C3 and Al2MgC2, presently without consideration of Al2CO. The ternary carbide Al2MgC2 was synthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…After a preliminary result recently published by Deffrennes et al [40], a reliable invariant decomposition temperature of Al2MgC2 is confirmed in the present study by the mean of Differential Thermal Analysis (DTA). In order to model the solubility of Mg in Al4C3, the standard enthalpy of formation of potential end-members phases is calculated by DFT.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…After a preliminary result recently published by Deffrennes et al [40], a reliable invariant decomposition temperature of Al2MgC2 is confirmed in the present study by the mean of Differential Thermal Analysis (DTA). In order to model the solubility of Mg in Al4C3, the standard enthalpy of formation of potential end-members phases is calculated by DFT.…”
Section: Introductionsupporting
confidence: 87%
“…The lack of reversibility is not surprising and commonly observed in the case of peritectic reactions. It is noteworthy that after DTA a few Al2MgC2 crystals could be found trapped in the middle of the biggest Al4C3 crystals [40]. Moreover, it is suggested that the films observed around the T2-Al2MgC2 phase in Fig.…”
Section: Resultsmentioning
confidence: 86%
“…The Ta crucibles were sealed inside vitreous silica containers under an absolute Ar pressure of 0.2 bar in order to avoid external oxidation and oxygen diffusion through the Ta crucibles during the heat treatment. The initial sample composition was not altered by magnesium evaporation as only a negligible fraction of Mg was needed to supply its equilibrium vapour pressure given the crucibles volume [22]. The samples were efficiently quenched by breaking the silica containers as soon as they were removed from the furnace.…”
Section: Synthesis Of T2-al2mgc2mentioning
confidence: 99%
“…However this hypothesis was not widely accepted; for example, Lu et al [21] pointed out that Al2CO is likely to be unstable in a Mg-rich melt based on thermodynamic calculations. In more recent studies [22,23], Al2MgC2 has been proposed to be the nucleant for grain refinement of Mg-Al alloys, although this phase was found [24] and synthesised [25] back in the 1990s. In the Al-C-Mg ternary system [13,25], Al4C3 and Al2MgC2 are both stable phases at 1000 K and Al4C3 is reported to be the equilibrium phase with Mg-Al liquid only when the Al content is more than 19 wt.%.…”
Section: Introductionmentioning
confidence: 99%